Prevalence and Characterization of Extended-Spectrum Beta-Lactamase-Producing Enterobacteriaceae Isolated in Canadian Hospitals: Results from CANWARD 2007 - Patricia J Baudry; Melissa McCracken; Philippe Lagacé-Wiens; Michael R Mulvey; George G Zhanel; Daryl J Hoban (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: The purpose of the present study was to determine the prevalence and molecular epidemiology of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae identified from Canadian hospitals in 2007. METHODS: Clinically significant isolates were collected as part of the Canadian Ward Surveillance Study (CANWARD 2007) from January to December 2007, inclusive, from 12 sentinel hospital centres across Canada. Minimum inhibitory concentrations were determined by broth microdilution, and putative ESBL isolates were confirmed by the Clinical and Laboratory Standards Institute disk diffusion method. Polymerase chain reaction and DNA sequencing were used to detect blaSHV, blaTEM, blaCTX-M and blaOXA-like genes. Strains were typed using pulsed-field gel electrophoresis. RESULTS: A total of 3.4% and 1.6% of Escherichia coli and Klebsiella pneumoniae, respectively, were identified as ESBL producers. Resistance to fluoroquinolones, doxycycline, trimethoprim/sulfamethoxazole and gentamicin occurred in 92.5% and 71.4%, 75.5% and 71.4%, 67.9% and 57.1%, and 58.5% and 57.1% of ESBL-producing E coli and K pneumoniae, respectively. A total of 90.6% and 71.4% of ESBL-producing E coli and K pneumoniae were identified as multidrug resistant. The CTX-M type was the predominant ESBL, with CTX-M-15 as the predominant genotype. A total of 81.7% ESBL-producers carried several beta-lactamase genes. Pulsed-field gel electrophoresis revealed that the majority of ESBL producers were not genetically related (less than 80% homology). Similar patient demographics were observed among both ESBL-producing E coli and K pneumoniae. CONCLUSION: CTX-M has become the most common enzyme among both ESBL-producing E coli and K pneumoniae. The spread of ESBLproducing bacteria across Canada is polyclonal and is not due to the clonal spread of a single strain.